KOMUNIKASI KOMUNIKASI SIMBOLIK SEMANGKA DALAM MENYUARAKAN AKSI BELA PALESTINA MELALUI MEDIA SOSIAL: Komunikasi Simbolik Semangka - Winda Meliana HASIBUAN (QAULAN : Jurnal Komunikasi dan Penyiaran Islam, 2023)
Symbolic Communication of Watermelon in Voicing Action to Defend Palestine Through Social Media. Social media is a very effective and efficient medium to use as a place to share or search for information. In using social media, there are various types of communication that can be carried out, including symbolic communication. The symbolic communication of watermelon which is used as a form of defense of Palestine using social media is very popular with users of social media platforms. This shows that there is a similarity in perception between the source and the target. This research was conducted to see the level of success of symbolic communication of watermelon via social media. The method in this research uses a qualitative approach with the library research method and a qualitative descriptive approach. The symbolic use of watermelon succeeded in conveying the message to the target and choosing social media as a place to convey information was the right choice. This research can open readers' horizons and is expected to trigger other researchers to continue research.